Pertumbuhan Pin Head Jamur Kuping Hitam (Auricularia Polytricha) Pada Media Tambahan Tetes Tebu Dengan Dosis Berbeda - Mahrus Ali; Hefdiyah Hefdiyah (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2021)
Mushroom growing media is the main source of mushroom production, so it needs attention, for example by changing the composition of the growing media such as adding supporting nutrients. Sugarcane drops are waste from the process of making sugarcane crystallization into sugar which is thought to have an effect on fungal growth. The purpose of this study was to determine the effect of molasses and the best dose on the growth of pin head A. polytricha. This research was carried out with the addition of molasses with different doses, namely, P0 (control), P1 (20 ml/liter), P2 (40 ml/liter), P3 (60 ml/liter) and P4 (80 ml/liter). This study uses One Way Anova analysis and 5% BNJ. Based on the results of the study, it was known that the addition of nutrients to the growing media of A. polytricha in the form of molasses had a fairly effective effect on the growth of the pin head of A. polytricha, namely at an additional dose of 80 ml/liter.